The Effects of Gold Deposition on Carbon Paste Electrode Modified with Zeolite for Voltametric Measurement of Arsenic(III) - ISNANIYAH WAHAB (NIM 10505042), HERKUSWYNA
Carbon paste electrode (CPE) has been commonly used in voltametric measurement for determination of metal ions. Addition of modifier is expected to improve the performance of carbon paste electrode. However, CPE cannot be used to analyze arsenic(III) voltammetrically. In this study, zeolite modified electrode deposited with gold was used for As(III) analysis. Electrodeposition of gold was conducted in HCl 1M electrolyte solution at constant potential of -500 mV (vs Ag/AgCl) for 120 s 10 times in a row. The effects of gold deposition on carbon paste electrode modified with zeolite has been used for Arsenic(III) measurement using square wave anodic stripping voltammetry. The results show that calibration curve is linear in the range of 0,1-10 ppm with detection limit of 77,02 ppb. Percent recovery of analysis is between 98,67%-109,14%.